Atrial fibrillation in athletes - Turagam, M. K.; Velagapudi, P.; Kocheril, A. G. (The American Journal of Cardiology, 2012)
Atrial fibrillation (AF) is the most common arrhythmia in the athletic community and is more frequently observed in middle-aged than in young athletes. Recent studies have shown that the prevalence of AF is higher in individuals who are involved in intense short-term training and long-term sports participation compared to general population of the same age although clear evidence about the causal relation between these conditions is lacking. Anatomic adaptation, chronic systemic inflammation, and alterations in the autonomic system are all possible explanations for the increased prevalence of AF in athletes. AF associated with sports is usually paroxysmal with occasional crisis. Treatment of AF in this population can be challenging because of a lack of randomized trials and clear guidelines. Antiarrhythmic agents are usually the preferred choice of drugs. Several reports of catheter ablation have demonstrated encouraging results. Further studies are needed to understand the mechanism of autonomic hyperactivation and its interaction with the atrial substrate to develop new ablation strategies in this group of patients. Also, studies on the intensity and duration of exercise that would negate the proarrhythmic cardiac effects are also warranted.